In SILICO Characterization of Technetium-99M Radiotracers: ADMET Properties and Protein Interaction Profiles - V. Trusova; U. Malovytsia; P. Kuznietsov; I. Yakymenko; G. Gorbenko (East European Journal of Physics)
The rational design of technetium-99m (99mTc)-based radiopharmaceuticals requires a nuanced understanding of how physicochemical properties influence in vivo behavior and molecular interactions. In this study, we employed an integrated in silico framework to characterize ten clinically relevant 99mTc-labeled tracers using ADMET prediction, molecular docking with functional proteins (albumin, insulin, lysozyme), and multivariate statistical analysis. The results revealed that polarity, hydrogen bonding capacity, and molecular flexibility critically govern both pharmacokinetic properties and protein-binding profiles. Tracers such as TcSES and TcTET, with low topological polar surface area and minimal binding affinity, were associated with rapid clearance and are well suited for dynamic imaging protocols. In contrast, compounds like TcDTPA and TcDIS demonstrated strong albumin interaction and metabolic stability, supporting their use in delayed-phase imaging. TcHYN emerged as a unique tracer, exhibiting extreme polarity and promiscuous high-affinity binding across multiple protein targets. Principal component analysis and hierarchical clustering grouped tracers into functionally distinct categories, highlighting structure-dependent design trends. Collectively, these findings suggest that combined ADMET-docking profiling offers a scalable strategy for preclinical evaluation and supports the development of safer, more targeted 99mTc-based radiopharmaceuticals.